Pengalaman belajar siswa madin dalam pembelajaran sharaf melalui metode presentasi dan diskusi - Sofi`, Utari Nur (Maliki Interdisciplinary Journal, 2025)
This study aims to describe the learning experience of Madrasah Diniyah (Madin) students in learning sharaf science through presentation and discussion methods. The focus of this study is how students respond, participate, and gain understanding of sharaf material through this approach. This study uses a descriptive qualitative approach with data collection techniques in the form of interviews. The results of the study indicate that the presentation and discussion method can increase students' active participation, foster self-confidence in expressing opinions, and deepen understanding of sharaf concepts. Although there are challenges such as differences in student ability levels and time constraints, this method is considered effective in creating interactive and meaningful learning. Thus, the presentation and discussion method can be used as an alternative sharaf teaching strategy that is oriented towards students' active and reflective learning experiences.